Toxic effects of some herbicides on the fatty acid profile of wheat varieties: A phytomicrobiome study - Karabulut, Fadime; Qanakci-Gulengul, Songul (wiley, 2022)
Arbuscular mycorrhizal fungi (AMF or AM fungi) are pervasive soil fungi in a symbiotic relationship with a large number of land plants. They rely on biological compounds (carbohydrate) provided by plants for growth and function, and in exchange, the fungi help plants obtain macroelements (e.g. phosphorus) from soil. Plant survival is improved by AMF symbiosis in a variety of unfavorable situations, for example, in chromium (Cr)-contaminated soil. They are a broader part of the food chain due to their migratory behavior and have an impact on human health. The AMF symbiotic association has been recorded to promote plant adaptation against Cr contamination, which could have significant implications and assist with phytoremediation and ecological restoration in Cr-polluted soils. This chapter is focused on the effect of AM fungi on reducing Cr toxicity in soil and the parameters that influence Cr tolerance in plants. Furthermore, AM fungi can improve the absorption area for nutrient uptake, enhance antioxidant-enzyme activity, improve the effect of chelate-assisted Cr on plant growth, improve protein synthesis by stimulating genes responsible, and ultimately reduce damage by releasing free ions in the soil solution. Plant Cr tolerance is improved by AMF association (symbiosis) by direct and indirect functions in Cr stability and transformation and nutrient acquisition regulated by AMF symbiosis-mediation mechanism and physiological control. Future studies should focus on omics strategies to improve molecular biological pathways and the physiological mechanisms underpinning Cr absorption and decontamination by using AM fungi applications with the aim of reclaiming Cr-contaminated soil and increasing agricultural production. © 2022 John Wiley & Sons Ltd. All rights reserved.
Keywords: Arbuscular mycorrhiza; Chromium; Fungus; Metals stress